Examining associations between human milk fatty acids, oligosaccharides, and early infant cognitive, language and motor development in the CHILD cohort study - Turner, Sarah E.; Roos, Leslie E.; Nickel, Nathan C.; Moraes, Theo J.; Turvey, Stuart E.; Simons, Elinor; Subbarao, Padmaja; Robertson, Bianca; Chikuma, Joyce; Goruk, Susan; Field, Catherine J.; Bode, Lars; et al. (Frontiers in Nutrition, 2025)
IntroductionHuman milk fatty acids and human milk oligosaccharides (HMOs) are milk components inconsistently associated with neurodevelopment. The objective of this research is to examine the link between fatty acids, HMOs and neurodevelopment.MethodsThis study includes a subset of 240 parent-infant pairs from the Edmonton site of the CHILD Cohort Study. At 3–4 months post-partum, breastfeeding parents provided a milk sample which was analyzed to identify 20 fatty acids and 19 HMOs. Research assistants administered the Bayley Scales of Infant and Toddler Development at 1 and 2 years of age, comprising cognitive, language and motor development scales (standardized to a mean of 100 and a standard deviation of 15; higher scores indicate better development). Adjusted linear regression was used to estimate the relationships between individual milk components or principal components and neurodevelopment, adjusting for maternal and infant factors. Interactions were tested with infant sex and maternal secretor status.ResultsAfter adjustment, the first fatty acid principal component, characterized by high saturated fat and low n-3 and n-6 fatty acids, was related to higher motor scores (β = 1.59; 95% CI: 0.75, 2.43). Higher concentrations of disialyllacto-N-tetraose were related to lower motor scores (β = −3.91, 95% CI: −5.81, −2.01). Higher concentrations of difucosyllacto-N-hexaose were related to higher language and motor scores for infants of maternal non-secretors, while higher concentrations of 3′-sialyllactose were related to higher scores for infants of maternal secretors.ConclusionBoth fatty acids and HMOs are related to early neurodevelopment. Maternal secretor status moderates the relationship between select HMOs and neurodevelopment.